Synthesis and Optical Properties of Red Carbon@(NH4)3ZnCl5 Hybrid Heterostructures - Walker Vinícius Ferreira do Carmo Batista; Aniely Pereira de Souza; Tais dos Santos Cruz; Dilton Martins Pimentel; Danila Graziele Silva de Avelar; Sarah Karoline Natalino Oliveira; Wanessa Lima de Oliveira; Danilo Roberto Carvalho Ferreira; Márcio Cesar Pereira; Rondinele Alberto dos Reis Ferreira; João Paulo de Mesquita (Compounds)
In this study, we report the synthesis and characterization of hybrid heterostructures composed of red carbon, an organic semiconductor polymer, and the perovskite (NH4)3ZnCl5. Red carbon was synthesized via the polymerization of carbon suboxide (C3O2), exhibiting strong light absorption and distinctive optical properties. The hybrid material was obtained by crystallizing (NH4)3ZnCl5 in the presence of red carbon, leading to significant modifications in the optical characteristics of the perovskite. Comprehensive analyses, including X-ray diffraction, FTIR spectroscopy, UV-vis spectroscopy, and cyclic voltammetry, confirmed the formation of a type I heterostructure with enhanced luminescence and potential for advanced optical applications. The energy band alignment suggests that red carbon can function effectively as both a hole and electron transport medium. This work underscores the potential of (NH4)3ZnCl5@red carbon hybrid heterostructures in the development of next-generation optoelectronic devices, including sensors and LEDs.